On developing a practical safety culture for the advanced reactor workforce: Experiences of working with sodium - LaBrier, Daniel; Pope, Chad; Marcum, Wade (Frontiers in Nuclear Engineering, 2023)
The Versatile Test Reactor (VTR) is meant to fill a need in the advanced nuclear reactor development community. Accelerated nuclear testing of fuels and materials is needed to allow designs to proceed. To accomplish this, a fast neutron spectrum is needed. To have a fast neutron spectrum, the reactor coolant needs to not only have excellent heat transfer properties to sufficiently cool the reactor core, but also not significantly slow neutrons down following their birth in the fission process. Sodium is an excellent coolant choice that can fulfill these needs and many others. Sodium is the sixth most abundant element in the Earth’s crust and can be acquired easily through simple chemical separation methods. Sodium, however, reacts when in contact with water and air, but with proper precautions, these scenarios can be avoided. Nuclear reactors that utilize molten sodium as a primary heat transfer medium (a.k.a. sodium-cooled fast-neutron reactors, or SFRs, Figure 1 [1]) provide unique challenges in their daily operation, and therefore require focused training for researchers, scientists, staff, and employees alike to understand these unique challenges. Therefore, a comprehensive understanding of sodium properties is needed by all personnel involved in the design, construction, operation, experiment planning and execution of SFRs. Additionally, several commercial advanced reactor designs are under development which will use sodium for the reactor coolant. These advanced reactor designs include the Natrium reactor from TerraPower & GE-Hitachi [2], the ARC-100 reactor from Advanced Reactor Concepts [3], and the Aurora reactor from Oklo [4].